Role of Embodied Movement in Assessing Creative Behavior in Early Childhood: A Focused Review. Issue 6 (December 2019) - Frith, Emily; Loprinzi, Paul D.; Miller, Stephanie E.
The controlled measurement of creative potential in early childhood is imperative for researchers seeking to fully understand the initial emergence and development of creativity. Evidence for original ideation has been demonstrated in infants as young as one year old, through their performance of movement-based, interactive creativity tasks. In this focused review of developmental research, we suggest that embodied movements and interactive play may uniquely facilitate creative thinking in early childhood (i.e., from birth to age six). From this review, we propose that embodied movement reinforces physical interactions that influence cognitions underlying creative behavior. Embodied creativity may supplement traditional creativity measures, as young children may be more inclined to represent their inner thoughts and experiences through movement rather than through language alone. Thus, we explored the importance of embodied creativity as a means of informing current researchers about the development of creativity, and we suggest future experimental research in this area.